The Role of Mediation in Increasing Intellectual Capital Based Innovative Behavior - Suahsti, Alfi; Sudarma, Ketut (Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the effect of learning organizations and leader-member exchange on innovative work behavior through work engagement. The sample of this study were 105 employees of the Central Java TVRI Public Broadcasting Institution. Sampling using the Probability Sampling technique that is proportionate random sampling. Data collection methods in this study used a questionnaire or questionnaire. The method of data analysis in this research is regression analysis and path analysis using IBM SPSS version 21 analysis tools. The results of this study indicate that there is a positive and significant direct effect between learning organizations and leader-member exchange on innovative work behavior. The results of this study also show the effect of a positive and significant indirect relationship between learning organizations and leader-member exchange on innovative work behavior with work engagement as a mediating variable.